2019
DOI: 10.1051/metal/2019045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical activation on the structure of pulverized coal and iron ore powder

Abstract: Morphologies and structures of pulverized coal and iron ore powder after mechanical activation were studied by SEM, XRD, FTIR and laser particle sizer. The microcrystalline structure of coal was found to be destroyed by mechanical activation via reducing the pile height and number of layers, and the organic structure of coal was altered through the destruction of the ether bond. Mechanical activation led to distortions and dislocations of the crystal lattice of iron ore, decreasing crystallite size, increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Only few studies have shown that coal gangue can improve its activity through mechanical activation, chemical activation, thermal activation, and microwave activation [7]. e effect of mechanical force in grinding would change the crystal structure and physical properties of minerals in coal gangue; the structures of the Al-O, Al-O-Si, and Si-O bonds on the particle surface are broken, and the surface hydroxyl is eliminated; this situation results in many chemical active points on the particle surface, increasing the surface activity and free energy of live materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have shown that coal gangue can improve its activity through mechanical activation, chemical activation, thermal activation, and microwave activation [7]. e effect of mechanical force in grinding would change the crystal structure and physical properties of minerals in coal gangue; the structures of the Al-O, Al-O-Si, and Si-O bonds on the particle surface are broken, and the surface hydroxyl is eliminated; this situation results in many chemical active points on the particle surface, increasing the surface activity and free energy of live materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%